Para administrar a ordem pública e a aplicação da lei: formas de policiamento em uma perspectiva comparada Brasil EstadosUnidos uma análise das experiências de Belo Horizonte, MG e Washington, D.C. - Marcus Vinicius Goncalves da Cruz (2005)
The process of introduction of the community policing in the "Metropolitan Police Department" in Washington, D.C., United States of America, and the Military Police of Minas Gerais, in Belo Horizonte, MG, Brazil was analyzed. The new institutionalism was adopted as theoretical approach, and the research question tried to analyze the police organizations to its institutional environment in three distinct levels: (i) general institutional environment; (ii) specific institutional environment; e (iii) technical environment, within pressures from coercitive, normative and mimetic mechanisms. Qualitative research was used by a comparative case study, and as data collection types; the participant as observer, face-toface interviews, and documental analysis. It was verified whether certain characteristics of its institutional environment had modified some police management practices, and its role of lawenforcement and order maintenance. Based on institutional context, criminal justice system and police structure, it was disclosing to the convergences and differences between them. As results it had a predominance of coercitive mechanisms and, institutional pressure formaintenance and social transformation are distinguished. To community policing be strengthen is necessary its full financing, involvement of all organization in the process, persuasion of the community and external partners. The United States case was distinguished by community participation, legislative pressure, "accountability" tools, outcomes measures, and emphasis in prevention. In Brazilian case, a better interaction between the lower and higher ranking members, to minimize the conflict between officers and patrol officers, changes in the organizational logic, from strong bureaucratic traces for a more flexible one and be taught to the general environment of crime and violence. The dynamics of the police organizations disclosed that as much the institutional environment as the technician environment equally influences adoption of community policing. However, the threats in theinstitutionalization remains: for the MPD, the involvement in activities of national security take it off of the public security, and, in the PMMG, the delay in accomplishing the changes and increase of crime rates, weakens the legitimacy of the police organization and intensify the resistance to community policing.